Bi- and trinuclear copper(I) complexes of 1,2,3-triazole-tethered NHC ligands: synthesis, structure, and catalytic properties - Gu, Shaojin; Du, Jiehao; Huang, Jingjing; Xia, Huan; Yang, Ling; Xu, Weilin; Lu, Chunxin (Beilstein Journal of Organic Chemistry, 2016)
A series of copper complexes (3–6) stabilized by 1,2,3-triazole-tethered N-heterocyclic carbene ligands have been prepared via simple reaction of imidazolium salts with copper powder in good yields. The structures of bi- and trinuclear copper complexes were fully characterized by NMR, elemental analysis (EA), and X-ray crystallography. In particular, [Cu2(L2)2](PF6)2 (3) and [Cu2(L3)2](PF6)2 (4) were dinuclear copper complexes. Complexes [Cu3(L4)2](PF6)3 (5) and [Cu3(L5)2](PF6)3 (6) consist of a triangular Cu3 core. These structures vary depending on the imidazolium backbone and N substituents. The copper–NHC complexes tested are highly active for the Cu-catalyzed azide–alkyne cycloaddition (CuAAC) reaction in an air atmosphere at room temperature in a CH3CN solution. Complex 4 is the most efficient catalyst among these polynuclear complexes in an air atmosphere at room temperature.
Keywords: copper; CuAAC reaction: N-heterocylic carbene; 1,2,3-triazole